KAJIAN POTENSI PEDAGANG KAKI LIMA (PKL) KULINER DALAM PENGEMBANGAN PARIWISATA DI MUARA BUNGO - Yudhi Novriansyah (Universitas Batanghari Jambi, 2018)
The objectives to be achieved in this study are (1). To know the characteristics of tourist visitors to the culinary in Muara Bungo (2). To know and study the region's Culinary through the mapping in Muara Bungo, (3). To know the potential that needs to be improved in Muara Bungo Culinary. Quantitative descriptive research survey approach. Respondents as many as 300 people, this research uses the sample withdrawal Convenience sampling/accidental sampling. The results showed: (1) the characteristics of the majority of visitors are the tourists of young children 21-30 years i.e. 55.3% where the dominance of male visitors 68.3%, and level of education Equal SLTA 57.3%, private sector job domination 59.7%, average earnings over 2 million dollars amounted to 42.7%. As for the origin of tourists in general around the mouth of the Bungo 55.7% or local tourists. Obtain information from the Culinary a 30% friends and visiting the site with your friends/family 90.7%; (2) the area's favorite Culinary tourists visit PKL is Pusparagam/Semagor field i.e. 37.3% and tourist favorite foods are Meatballs/58%, and the Miso favorite drink juices 74% and Crispy Banana snack 42.7%; (3) the main reason tourists visit due to the price of 27.7%. Potential needs to be improved is the Culinary and infrastructure improvements, namely 61% to give convenience to tourists. It is recommended to the Government to increase the potential of Bungo in 5 main areas of Culinary with revamping the facility/infrastructure that is 93%. Keywords: Culinary, Tourism, Muara Bungo